María Elvira Ríos, Gonzalo Maire, Pablo Álvarez, Isabel Cabañas y Matilde Gálvez, coords. 2019. Nuevos diálogos. Asia y África desde la mirada latinoamericana. Ciudad de México: El Colegio de México. Ebook ISBN 9786076285787 - Kakozi Kashindi, Jean Bosco; Rivera Espinoza, Manuel (Estudios de Asia y África, 2021)
María Elvira Ríos, Gonzalo Maire, Pablo Álvarez, Isabel Cabañas y Matilde Gálvez, coords 2019. Nuevos diálogos. Asia y África desde la mirada latinoamericana. Ciudad de México: El Colegio de México. Ebook ISBN 9786076285787